Gambaran Perubahan Perilaku Pada Klien Pengguna Napza Setelah Diterapi Di Klinik Pratama BNN Kabupaten Sumenep Tahun 2017 - Aspandi Aspandi (Fakultas Ilmu Kesehatan, 2018)
Narcotics abuse in Indonesia has now been established by the government as a very dangerous issue for the Indonesian nation. The projection of the number of drug abuse in the past year has continued to increase. So there needs to be a maximum and integrated countermeasures, to reduce the number of drug abuse. The public's assumption that drug abuse is a criminal act that is a family disgrace and imprisonment and ostracism, does not solve the problem. The effort of handling it through the rehabilitation process is thorough and sustainable until it recovers. The purpose of this study is to determine the effectiveness of rehabilitation to change the behavior of drug abuse victims in Rehabilitation Clinic Narcotics Agency Sumenep.The subjects of the experimental group is the client who perform rehabilitation clinic Rehabilitation BNN Sumenep regency starting from january-june 2017 as many as 28 clients. The technique used is Total Population is a technique of determining the sample by means of all members of the population used as a sample (Setiadi, 2008) The design of this research using descriptive method. Number of samples used by 28 clients about behavior in drug user, with simple random sampling technique. The variables studied were behavioral changes in the clients of drug users who had been receiving outpatient rehabiliation at BNN K Sumenep Rehabilitation Clinic. The results of this study indicate that from 28 respondents who have received outpatient rehabilitation, as many as 23 people (82%) respondents who have successfully changed the behavior to be good It is expected that officers and families continue to provide support to respondents to always behave well, so that respondents can maintain behavior change towards good and positive.